Subsidy policies of Vietnam : - Dordi, Claudio (National political publishing house, 2008)
This book comprises the two following researches: Vietnam's agricultural domestic support and subsidy policies and measures; The removal of illegal subsidies after the accession of Vietnam to the WTO: an impact assessment in electronics, textiles and garment industries.